The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/627352
|View full text |Cite
|
Sign up to set email alerts
|

Early Invasive Cancer and Partial Intraoperative Electron Radiation Therapy of the Breast: Experience of the Jules Bordet Institute

Abstract: Objectives. The aim of this prospective phase II study is to evaluate the treatment of early-stage breast cancer (T1 N0) with intraoperative electron radiation therapy (IOERT) in terms of local control, early complications, and cosmesis. Patients and Methods. From February 2010 to February 2012, 200 patients underwent partial IOERT of the breast. Inclusion criteria were unifocal invasive ductal carcinoma, age ≥40 years, histological tumour size ≤20 mm, and no lymph node involvement. A 21 Gy dose was prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
6
0
5
Order By: Relevance
“…This finding is lower than those of previous studies that reported a 53%‐57% rate of concordance for MRI . The 5 mm cutoff that was used in these previous studies corresponds to a stage migration in T1 breast tumors (T1a, T1b, T1c) and could represent a substantial discordance in the treatment plan, especially for IORT patient selection . A 2 mm cutoff of tumor size seems to be much more reasonable for the BIT to better estimate preoperative staging.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This finding is lower than those of previous studies that reported a 53%‐57% rate of concordance for MRI . The 5 mm cutoff that was used in these previous studies corresponds to a stage migration in T1 breast tumors (T1a, T1b, T1c) and could represent a substantial discordance in the treatment plan, especially for IORT patient selection . A 2 mm cutoff of tumor size seems to be much more reasonable for the BIT to better estimate preoperative staging.…”
Section: Discussionmentioning
confidence: 57%
“…In our clinic, breast MRI is generally performed to rule out multifocal and/or multicentric disease in patients with TS up to 2 cm prior to intraoperative radiation therapy (IORT) …”
Section: Introductionmentioning
confidence: 99%
“…Figura 1. Diagrama de flujo para la identificación y selección de estudios sobre RIO Los resultados estéticos son evaluados por 6 estudios 35,38,[50][51][52][53] y la calidad de vida percibida por las mujeres en uno de los estudios seleccionados 50 . La seguridad del personal sanitario es abordada en uno de los estudios seleccionados 54 , y la evaluación económica de la RIO por tres 6,55,56 .…”
Section: Resultsunclassified
“…Se han seleccionado 21 estudios para la descripción y análisis de la seguridad de la RIO 10,11,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] , uno específico sobre la aparición de cicatrices hipertróficas 42 , otro sobre seguridad cardíaca 43 , dos estudios que abordan el correcto posicionamiento del emisor de radiaciones 46,47 y dos estudios que debaten la aparición de segundas neoplasias 44,45 .…”
Section: Seguridad De La Riounclassified
“…When the resection leaves behind a thin region of unresected tumor cells (either microscopic or macroscopic), the use of intraoperative high‐dose‐rate brachytherapy (IORT‐HDR), low energy photons, or megavoltage electrons can provide a therapeutic dose to the tumor bed while minimizing damage to distal tissues. Accordingly, IORT has found several clinical applications using a number of different delivery devices for sites such as sarcomas,1, 2, 3 breast,4, 5 recurrent head and neck cancer,6 pancreatic cancer,7 locally advanced and recurrent GYN tumors,8 rectal cancers,9, 10 and genitourinary cancers 11…”
Section: Introductionmentioning
confidence: 99%